1991
DOI: 10.1111/j.1476-5381.1991.tb09787.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of endothelin‐1 and NG‐nitro‐l‐arginine methyl ester on regional haemodynamics in conscious rats with streptozotocin‐induced diabetes mellitus

Abstract: 1 Resting haemodynamic status and responses to endothelin-1 (0.004, 0.04, 0.4 nmol kg-1) and NG-nitro-L-arginine methyl ester (L-NAME, 10mg kg-1) were assessed in conscious, Wistar rats treated with streptozotocin (STZ) to induce diabetes mellitus, and in control animals treated with saline. 2 In the resting state, STZ-treated rats had a bradycardia relative to control animals (291 + 13 and 337 + 10 beats min-, respectively), but mean arterial blood pressures were the same in the two groups (STZ-treated 109 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 60 publications
5
48
1
Order By: Relevance
“…Thus, for renal and mesenteric vascular beds, where flow is increased by diabetes, ET-mediated vasoconstriction was increased. However, in the hindlimb circulation, where flow decreases with diabetes, the vasoconstrictor response was relatively muted [50]. The data for sciatic nerve agree with the latter finding, as the effects of BQ-123 suggest that there would already be much greater local ET production and vasoconstriction with diabetes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, for renal and mesenteric vascular beds, where flow is increased by diabetes, ET-mediated vasoconstriction was increased. However, in the hindlimb circulation, where flow decreases with diabetes, the vasoconstrictor response was relatively muted [50]. The data for sciatic nerve agree with the latter finding, as the effects of BQ-123 suggest that there would already be much greater local ET production and vasoconstriction with diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…Diabetic vessels have reduced ET sensitivity [44-461, perhaps caused by a down-regulation of receptors [47,48] or transduction mechanisms [49] in response to chronic exposure. Regional blood flow patterns for bolus ET injection are altered by diabetes in conscious rats [10,50] but the changes are complex, suggesting tissue heterogeneity. Thus, for renal and mesenteric vascular beds, where flow is increased by diabetes, ET-mediated vasoconstriction was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our own laboratory have shown lower HR and reduced systolic blood pressure in conscious STZ-induced diabetic rats (44). However, a few studies from other laboratories have reported unchanged (5,6,24) or increased blood pressure in diabetic rats (22). Although the reasons for these discrepancies are not very clear, it is likely that differences in the duration of diabetes, use of anesthetics, and varied techniques employed for measurement of blood pressure may have contributed to the disparities in the observed results (25).…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, it is not known what the effect would be on ET-1 responses of bathing solutions appropriately adjusted for the differences in the composition of the extracellular fluid (including osmolality) of control and STZtreated rats. Indeed, no such comparative in vitro studies with adjusted bathing solutions have been performed (Kiff et al, 1991a). Also, changes in aortic endothelial cell function may not reflect changes in other vascular beds.…”
Section: Discussionmentioning
confidence: 99%